Manajemen Pendidikan Anak Usia Dini - Dewi, Diana Try Buana Tungga; Darmiyanti, Astuti (Yayasan Rahmat Islamiyah, 2023)
Management of early childhood education is to ensure that the management of educational institutions runs smoothly. One indicator of good PAUD management is the ability to provide effective PAUD services. The above problems greatly affect the function of early childhood education. In its development, pragmatic aspects such as competition, institutional image and the like emerge as determining factors in the management of early childhood education institutions. As a result, many early childhood education institutions no longer function according to their original purpose.